Evaluation of internet of Things Devices and Management tools. (International Journal of Engineering and Computer Science, 2017)
Abstract— Trade 4.0 with web of Things (IoT) is that the next wave in technology revolution that is predicted to change our daily life. This digitalization has nice impact on all the domains (energy, healthcare, transportation, producing etc.) additionally to the data and Communication Technologies (ICT) sector. In IoT eventualities, various sensors measure and report many phenomena and wide-ranging IoT solutions area unit deployed to gather huge quantity of information. IoT platforms, like Amazon AWS, IBM Watson or Microsoft IoT Suite, are offered to help the event of such services/applications. However, one in all the most important challenges featured by IoT solutions suppliers is that the superintendence and management of the large range of deployed sensors/devices. Presumably, the magnitude and heterogeneousness of the IoT systems makes it troublesome to manage them with typical IT management tools and techniques. New techniques and tools ought to be explored and developed or the standard management solutions ought to be adapted to the new challenges. During this paper, we have a tendency to establish and formulate the essential challenges of IoT device management and supervision, review the particular progressive IoT device management and superintendence techniques and tools obtainable on the market, and in short evaluate their features and typical use cases.Keywords- internet of Things; Device Management; Platforms; Sensors.